Successful treatment of severe COVID-19 pneumonia, a case series with simultaneous interleukin-1 and interleukin-6 blockade with 1-month follow-up. (September 2022) - Haibel, Hildrun; Poddubnyy, Denis; Angermair, Stefan; Allers, Kristina; Vahldiek, Janis L.; Schumann, Michael; Schneider, Thomas
Interleukin (IL)-6 and IL-1 blockade showed beneficial results in patients with severe COVID-19 pneumonia and evidence of cytokine release at the early disease stage. Here, we report outcomes of open-label therapy with a combination of blocking IL-6 with tocilizumab 8 mg/kg up to 800 mg and IL-1 receptor antagonist anakinra 100–300 mg over 3–5 days. Thirty-one adult patients with severe COVID-19 pneumonia and signs of cytokine release, mean age 54 (30–79) years, 5 female, 26 male, and mean symptom duration 6 (3–10) days were treated. Patients with more than 10 days of symptoms, evidence of bacterial infection/elevated procalcitonin and other severe lung diseases were excluded. Computed tomography (CT) scans of the lung were performed initially and after 1 month; inflammatory activity was assessed on a scale 0–25. Twenty-five patients survived without intubation and mechanical lung ventilation, two patients died. C-reactive protein decreased in 19/31 patients to normal ranges. The mean activity CT score decreased from 14 (8–20) to 6 (0–16, n  = 16). In conclusion, most of our patients recovered fast and sustained, indicating that early interruption of cytokine release might be very effective in preventing patients from mechanical ventilation, death, and long-term damage.